Síntese de eletrocatalisadores para células a combustível visando geração de energia limpa - Maranghetti Filho, Antonio Carlos (Universidade Federal de São Carlos, 2022)
Population growth causes an increase in energy demand. Gradually more the world's energy matrices have adopted clean sources of energy, an example is the electrical energy produced from fuel cells. This study brings a brief discussion about how these electrochemical devices operate and aimed the study of the synthesis and application of palladium-based catalysts that favor anodic reactions in fuel cells which convert chemical energy into electrical energy. Therefore, palladium and rhodium-based nanoparticles were developed in different atomic proportions, by the sodium borohydride reduction method. The metal mass composition of these materials was set at 20%, with Vulcan XC72 carbon used as a support. For the characterization of the prepared materials, physical and chemical tests were carried out, such as: X-ray diffraction (XRD), chronoamperometry (CA), cyclic voltammetry (CV), in addition to fuel cell tests. Although the electrochemical tests (CA and CV) indicated better results for the PdRh materials (50:50), the PdRh/C in the 90:10 atomic ratio showed better values of maximum power density (MPD), 20.6 mW cm–2, which indicates good synergy between the materials due to the oxophilic character of Rh and the ability to desorb Had species that accumulate in the catalyst and decrease the fuel oxidation efficiency.
Fuel cell electrocatalysts synthesis aiming clean energy generation
Keywords: Energia limpa; Célula a combustível; Eletrocatalisadores de Pd; Formiato; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA